Archaeoastronomical study of Christian churches in Fuerteventura - Muratore, María Florencia (2021)
We present preliminary results of an archaeoastronomical study of the orientations of the colonial Christian churches on the island of Fuerteventura, in the Canary Islands, Spain, mostly built from the period of the Norman conquest in the 15th century to the 19th century. Our goal is to analyze the possible influence of astronomical events on the orientation of these churches. Preliminary results suggest that the vast majority of the island’s religious constructions have their axes oriented within the solar range, between the extreme azimuths of the annual movement of the Sun as it crosses the local horizon. This differs from what was found on the islands of Lanzarote and La Gomera (also in the Canaries) previously studied.